Pengelolaan Sentra Persiapan di Kelas B Taman Kanak-Kanak Mujahidin 2 Pontianak : Management of Preparation Centers in Class B Mujahideen Kindergarten 2 Pontianak - Amara Delvia; Iin Maulina; Yuniarti (Universitas Ngudi Waluyo, 2024)
The aim of the research is to describe the planning, implementation, evaluation, and supporting and inhibiting factors of the preparation center learning model for class B children at the Mujahidin 2 Pontianak Kindergarten. Descriptive method with a qualitative approach. The research subjects were preparatory center teachers. Data collection uses observation, interview and documentation techniques. The technique for checking data validity is triangulation. Based on the research results, a summary of the planning for the preparatory center learning model can be carried out by first preparing the teacher's Daily Learning Implementation Plan (RPPH), Weekly Learning Implementation Plan (RPPM) and Learning Implementation Plan (RPPS) and preparing learning tools and media, implementing the preparatory center learning model carried out with active learning and taking steps such as playing environment steps, initial steps (before playing), steps during play and steps after playing. After the lesson ends, the children sit in a circle and close the lesson. Evaluation uses daily evaluation checklists, portfolios and periodic reports each semester. The supporting factor is that the teacher actively provides motivation during the learning process. The inhibiting factors are the lack of main tools and children who cannot stay still during the learning process. Thus, this research shows that the planning, implementation and evaluation of the preparation of the management center in class B of Mujahidin 2 Kindergarten (TK) was declared good. ABSTRAK Tujuan Penelitian untuk mendeskripsikan perencanaan, pelaksanaan, evaluasi, serta faktor pendukung dan penghambat model pembelajaran sentra persiapan pada anak kelas B di Taman Kanak-Kanak Mujahidin 2 Pontianak. Metode deskriptif dengan pendekatan kualitatif. Subjek penelitian adalah guru sentra persiapan. Pengumpulan data menggunakan teknik observasi, wawancara dan dokumentasi. Teknik pemeriksaan keabsahan data adalah triangulaasi. Berdasarkan hasil penelitian dapat disimpulkan perencanaan model pembelajaran sentra persiapan dilakukan dengan terlebih dahulu guru menyusun Rencana Pelaksanaan Pembelajaran Harian (RPPH), Rencana Pelaksanaan Pembelajaran Mingguan (RPPM) dan Rencana Pelaksanaan Pembelajaran (RPPS) dan menyiapkan alat dan media pembelajaran, pelaksanaan model pembelajaran sentra persiapan dilakukan dengan pembelajaran aktif dan melaksanakan pijakan-pijakan seperti pijakan lingkungan main,pijakan awal (sebelum main), pijakan saat main dan pijakan setelah main. Setelah pembelajaran berakhir, anak duduk melingkar dan menutup pembelajaran. Evaluasi menggunakan ceklis evaluasi harian, portofolio dan laporan periodik tiap semester. Faktor pendukung yaitu guru aktif memberi motivasi saat proses pembelajaran. Faktor penghambat yaitu kurangnya jumlah alat main dan anak yang tidak bisa diam saat proses pembelajaran. Dengan demikian, penelitian ini menunjukkan bahwa perencanaan, pelaksanaan dan evaluasi pada pengelolaan sentra persiapan di kelas B Taman Kanak-Kanak (TK) Mujahidin 2 dinyatakan baik.